Analisis Pengaruh Pelaksanaan Program Kota Layak Anak Klaster Kesehatan terhadap Pelayanan Kesehatan Anak Usia 0-59 Bulan - Samsuddin, Samsuddin (Health Information : Jurnal Penelitian, 2017)
City fit for children program focuses on 4 main efforts: children health, children education, children protection, and children participation. Kendari is one of cities having commitment to do the program. To strengthen management of city fit for children program Kendari government through Family Planning and Women Empowerment Agency have established task force of city fit for children involving all stakeholders particularly Health office. This research was intended to identify effect of city fit for children program Health cluster on children health service U 0-59 Mounth in Kendari. This was non-experimental research with descriptive comparative approach and quantitative cohort retrospective design. It was conducted in three subdistricts in Kendari in January to February 2015 with sample of 381 respondents using instrument of 2007 Riskesdas questionnaire and KLA evaluation sheet of 2013. Paired t test indicated that during implementation of city fit for children program there is some indicator variable of increasing children health improvement including immunization service coverage with p value of 0.04 in 2014 to 2015, K4 service coverage with p value of 0.02 in 2014 to 2015 and exclusive breast milk with p value of 0.02 in 2013 to 2014. There is increase in children health status during implementation of city fit for children program particularly in immunization coverage and exclusive breast milk.